The Scope of Safety Warrants Under the Children, Young Persons, and Their Families Act 1989 - Beverley, P (Victoria University of Wellington Law Review, 1997)
The Children, Young Persons, and Their Families Act 1989 ("CYPF Act") recognises that the interests of a child will be generally best served within the family unit. This recognition is subject to the qualification that a child should be removed from that unit whenever there is an unacceptable risk of harm to that child. This analysis will consider one mechanism provided by the Act to facilitate such removal, and the effect of the Court of Appeal decision in R v Kahu.